PERAN KEPEMIMPINAN DALAM MANAJEMEN PERUBAHAN ORGANISASI - Mansyur, Umar; Putri, Almanda Rizkia; Bunga, Bunga; Hardiawan, Imran Zulfi; Mutaqinski, M. Bangkit; Mahal, Syakila Dzulfy Taz (Westscience Press, 2026)
Organizational change is an inevitable phenomenon in response to the dynamic development of internal and external organizational environments. In dealing with these changes, leadership plays a crucial role in determining the success of organizational change management. This paper aims to examine and analyze the role of leadership in organizational change management based on a review of relevant academic literature. The research method used is a qualitative approach with a literature study (library research), where data are obtained from SINTA-accredited national journals, international journals, and relevant reference books accessed through Google Scholar. The collected data are analyzed using descriptive qualitative analysis to understand the role of leaders in planning, directing, communicating, and managing resistance to organizational change. The discussion results indicate that leadership has a strategic role in determining the direction of change, building effective communication, managing human resources, and shaping an adaptive organizational culture. Effective leadership enables organizational change management processes to run optimally and supports the achievement of sustainable organizational goals.